On MIMO channel capacity an intuitive discussion. - Stoica, P. (IEEE Signal processing magazine)
For a general MIMO communication channel, the use of the linear minimum mean-squared-error (LMMSE) estimator followed by the separate substream decoding is not a capacity-wise optimal scheme. In this paper, the author presents analytical computations of the MIMO channel capacity. The article relates the capacity to the covariance matrix of the LMMSE estimate that provides a clear interpretation of the concept of capacity as well some optimal transceiver design schemes that aim to achieve channel capacity.